2021
DOI: 10.3389/fcell.2021.779432
|View full text |Cite
|
Sign up to set email alerts
|

GSDMD Mediates LPS-Induced Septic Myocardial Dysfunction by Regulating ROS-dependent NLRP3 Inflammasome Activation

Abstract: Myocardial dysfunction is a serious consequence of sepsis and contributes to high mortality. Currently, the molecular mechanism of myocardial dysfunction induced by sepsis remains unclear. In the present study, we investigated the role of gasdermin D (GSDMD) in cardiac dysfunction in septic mice and the underlying mechanism. C57BL/6 wild-type (WT) mice and age-matched Gsdmd-knockout (Gsdmd-/-) mice were intraperitoneally injected with lipopolysaccharide (LPS) (10 mg/kg) to mimic sepsis. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…When the dose of LPS injected into the animal is large enough, the animal will show physiological and biochemical changes. After the use of drugs to inhibit the related myocardial inflammatory pathway, the mouse heart dysfunction caused by LPS could also be improved to a certain extent ( Abd et al, 2021 ; Dai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…When the dose of LPS injected into the animal is large enough, the animal will show physiological and biochemical changes. After the use of drugs to inhibit the related myocardial inflammatory pathway, the mouse heart dysfunction caused by LPS could also be improved to a certain extent ( Abd et al, 2021 ; Dai et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is shown to have beneficial effects ( 27 , 28 ), the therapeutic effects of berberine for sepsis-induced cardiac dysfunction have not been studied in detail to date. In the present study, mice were intraperitoneally injected with 10-mg/kg body LPS to induce cardiac dysfunction, which is a widely accepted noninvasive reliable model ( 29 , 30 ). After 6 h of LPS treatment, cardiac function was severely impaired, as evidenced by the decreases in LVEF and LVFS and the increase in myocardial injury markers.…”
Section: Discussionmentioning
confidence: 99%
“… 109 Activation of phosphorylated Akt also provides a promising research basis for the treatment of SIMI. 110 There is a study demonstrated that the NLRP3 inflammasomes were activated in SIMI, and TXNIP 111 as well as GSDMD 112 mediated the activation of NLRP3 inflammasomes. However, the activation of NLRP3 inflammasomes depends on the production of reactive oxygen species (ROS).…”
Section: Over-inflammation In Simimentioning
confidence: 99%
“…However, the activation of NLRP3 inflammasomes depends on the production of reactive oxygen species (ROS). 112 Proteomic studies have also shown that inflammatory responses in sepsis are induced by activation of the TLR4/NLRP3 signaling pathway. 113 Therefore, therapeutic strategies based on the inhibition of NLRP3 inflammasome will be the key to our study of SIMI.…”
Section: Over-inflammation In Simimentioning
confidence: 99%